2018
DOI: 10.1161/jaha.118.009158
|View full text |Cite|
|
Sign up to set email alerts
|

High‐Normal Thyroid‐Stimulating Hormone Shows a Potential Causal Association With Arrhythmia Recurrence After Catheter Ablation of Atrial Fibrillation

Abstract: BackgroundHypothyroidism has been shown to contribute to enhanced atrial arrhythmogenesis, resulting in atrial fibrillation (AF) development in animal models and clinical populations. We aimed to elucidate whether high thyroid‐stimulating hormone (TSH) levels are related to outcomes of catheter ablation of AF.Methods and ResultsOf 477 consecutive patients who underwent first‐time pulmonary vein isolation–based radiofrequency catheter ablation of AF, 456 with TSH above the lower limit of the normal range (age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 22 publications
(29 reference statements)
2
16
0
3
Order By: Relevance
“…Wei et al [17] also suggested that TSH was not an independent predictor of LA arrhythmia recurrence in their population, which is consistent with our results. In contrast, Morishima et al [9] demonstrated that patients with high TSH levels, even on the high-end of the normal range, could be exposed greater to a risk of AF recurrence in a Japanese population. In the report of Morishima et al [9], patients with a history of thyroid diseases or medications for thyroid diseases were not excluded.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Wei et al [17] also suggested that TSH was not an independent predictor of LA arrhythmia recurrence in their population, which is consistent with our results. In contrast, Morishima et al [9] demonstrated that patients with high TSH levels, even on the high-end of the normal range, could be exposed greater to a risk of AF recurrence in a Japanese population. In the report of Morishima et al [9], patients with a history of thyroid diseases or medications for thyroid diseases were not excluded.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, Morishima et al [9] demonstrated that patients with high TSH levels, even on the high-end of the normal range, could be exposed greater to a risk of AF recurrence in a Japanese population. In the report of Morishima et al [9], patients with a history of thyroid diseases or medications for thyroid diseases were not excluded. Although TSH reflects the status of the thyroid, it is influenced by drugs and nonthyroidal disease [18].…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, TH affect the outcomes after an invasive treatment of AF. Accordingly, high circulating T 3 , as well as high-normal T 4 or lower TSH levels, have been associated with AF recurrence after an arrhythmogenic foci ablation [23,[88][89][90][91]. Free T 4 levels influence the success rate of ablation procedures even in the normal range.…”
Section: Thyroid Status Imbalance Promoting Afmentioning
confidence: 99%
“…First of all, it is achieved by isolation of pulmonary veins (PVs), which usually function as sources of AF, causing premature contractions. Electrical isolation of PVs has been shown to be up to approximately 80 % successful in significantly reducing the frequency and duration of AF in patients who do not tolerate AF [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest a close association of hypothyroidism history with the occurrence of AF in patients. However, there is very little data in the literature on the effect of thyroid hormone levels on the effectiveness of RFA [5,9,[13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%